Monitoring the thermally induced transition from sp3-hybridized into sp2-hybridized carbons. (February 2021) - Schüpfer, Dominique B.; Badaczewski, Felix; Peilstöcker, Jan; Guerra-Castro, Juan Manuel; Shim, Hwirim; Firoozabadi, Saleh; Beyer, Andreas; Volz, Kerstin; Presser, Volker; Heiliger, Christian; Smarsly, Bernd; Klar, Peter J.
Abstract: The preparation of carbons for technical applications is typically based on a treatment of a precursor, which is transformed into the carbon phase with the desired structural properties. During such treatment the material passes through several different structural stages, for example, starting from precursor molecules via an amorphous phase into crystalline-like phases. While the structure of non-graphitic and graphitic carbon has been well studied, the transformation stages from molecular to amorphous and non-graphitic carbon are still not fully understood. Disordered carbon often contains a mixture of sp 3 -, sp 2 -and sp 1 -hybridized bonds, whose analysis is difficult to interpret. We systematically address this issue by studying the transformation of purely sp 3 -hybridized carbons, that is, nanodiamond and adamantane, into sp 2 -hybridized non-graphitic and graphitic carbon. The precursor materials are thermally treated at different temperatures and the transformation stages are monitored. We employ Raman spectroscopy, WAXS and TEM to characterize the structural changes. We correlate the intensities and positions of the Raman bands with the lateral crystallite size L a estimated by WAXS analysis. The behavior of the D and G Raman bands characteristic for sp 2 -type material formed by transforming the sp 3 -hybridized precursors into non-graphitic and graphitic carbon agrees well with that observed using sp 2 -structured precursors. Graphical abstract: Image 1